Inflammasome-Mediated Inflammation in Liver Ischemia-Reperfusion Injury - Mónica B. Jiménez-Castro; María Eugenia Cornide-Petronio; Jordi Gracia-Sancho; Carmen Peralta (Cells, 2019)
Ischemia-reperfusion injury is an important cause of liver damage occurring during surgical procedures including hepatic resection and liver transplantation, and represents the main underlying cause of graft dysfunction and liver failure post-transplantation. To date, ischemia-reperfusion injury is an unsolved problem in clinical practice. In this context, inflammasome activation, recently described during ischemia-reperfusion injury, might be a potential therapeutic target to mitigate the clinical problems associated with liver transplantation and hepatic resections. The present review aims to summarize the current knowledge in inflammasome-mediated inflammation, describing the experimental models used to understand the molecular mechanisms of inflammasome in liver ischemia-reperfusion injury. In addition, a clear distinction between steatotic and non-steatotic livers and between warm and cold ischemia-reperfusion injury will be discussed. Finally, the most updated therapeutic strategies, as well as some of the scientific controversies in the field will be described. Such information may be useful to guide the design of better experimental models, as well as the effective therapeutic strategies in liver surgery and transplantation that can succeed in achieving its clinical application.